Uplink CFO compensation for FBMC multiple access and OFDMA in a high mobility scenario - González, Gustavo José (2014)
We study in this work CFO compensation methods for two multicarrier multiple access techniques in a high mobility scenario. In particular, we consider orthogonal frequency division multiple access (OFDMA) and filter bank multicarrier multiple access (FBMC-MA). The main motivation for this study is not only the different sensitivity these multicarrier techniques have to CFO but also the different methods they use to reduce CFO effect. In a high mobility scenario the CFO is re-estimated to follow its variation. We show that the frequency at which the CFO is re-estimated has a strong influence in the performance and the complexity of the proposed compensation methods. Additionally, we present a low-complexity CFO compensation method for OFDMA that employs a better approximation of the intercarrier interference than previous approaches. Regarding FBMC-MA, we introduce an extension of a CFO-compensation method that allows to consider a multitap channel equalizer. Finally, using simulations, we compare the performance of the compensation methods over several channel and time-varying CFO conditions.